Cultural Accounting in the Ogoh-Ogoh Tradition: A Symbolic Interactionist Approach - Kusila Meyrin Rossalia; Ana Sopanah; Syamsul Bahri (Politeknik Ganesha Medan, 2025)
This study aims to explore the practice of cultural accounting in the Balinese Ogoh-Ogoh tradition by revealing the values of local wisdom that shape the financial management system of the indigenous community. This study uses an interpretive qualitative methodology with a symbolic interactionism approach. The setting of this study was conducted in Banjar Gemeh, Denpasar, Bali, and involved nine (9) main informants determined through purposive sampling techniques. Data collection was carried out through non-participatory observation, semi-structured interviews, and documentation. Data analysis was carried out in five stages: narrative description, interaction process, symbol meaning, division of themes and categories of meaning, and analysis of thoughts, self, and society. The results of the Ogoh-Ogoh tradition research contain local wisdom values of ngayah, menyama braya and Tri Hita Karana. In addition, this study also reveals the accounting financing carried out by the banjar community as a form of social and symbolic accountability to local wisdom values. The value of ngayah is reflected in voluntary participation and awareness in providing funds without imbalance, while menyama braya strengthens solidarity and collective responsibility in financing, and Tri Hita Karana serves as the basis for harmony in managing human, natural, and spiritual resources. These three values influence the way communities organize, allocate, and account for funds socially and symbolically. This study contributes by uncovering symbolic and social accountability embedded in Ogoh-Ogoh cultural financing, beyond technical cost analysis used in prior studies. The novelty of this research lies in emphasizing symbolic interactionism to explain how cultural values shape accounting practices in a local community context. This study highlights the importance of integrating local cultural values into accounting systems to form relevant, contextual, and sustainable practices.